Antagonistic Microbial Interactions: Contributions and Potential Applications for Controlling Pathogens in the Aquatic Systems - Feichtmayer, Judith; Deng, Li; Griebler, Christian (Frontiers in Microbiology, 2017)
Despite the active and intense treatment of wastewater, pathogenic microorganisms and viruses are frequently introduced into the aquatic environment. For the majority of human pathogens, however, this is a rather hostile place, where starvation, continuous inactivation and decay usually take place, rather than successful reproduction. Nevertheless, pathogenic microorganisms can be detected with great diversity - especially in surface waters receiving wastewater. The extent of pathogen survival depends largely on abiotic factors such as irradiation, changes in water ionic strength, temperature and redox state. In addition, inactivation is enhanced by biotic interactions in the environment. Even though biotic antagonistic interactions are known for a long time now, some of the underlying processes and mechanisms are still not fully understood. Others are well appreciated and applied increasingly. Our review compiles and discusses the presently known biotic interactions between autochthonous microbes and pathogens introduced into the aquatic environment including protozoan grazing, virus-induced bacterial cell lysis, antimicrobial substances and predatory bacteria. An overview is provided on the present knowledge, as well as on obvious research gaps. Individual processes that appear promising for future application in the aquatic environment are presented and discussed.